2013
DOI: 10.1128/jcm.02548-12
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter canis Bacteremia in a Patient with Fever of Unknown Origin

Abstract: A 57-year-old woman with common variable immune deficiency and liver failure of unknown etiology presented with recurrent fevers over a 5-month period. She was found to have Helicobacter canis bacteremia. Immunocompromised hosts with exposure to cats or dogs may be at risk for infection with this organism, which may be challenging to diagnose. CASE REPORTA 57-year-old woman from Montana was referred to our institution for Infectious Diseases consultation for recurrent fever and chills for 3 months. She had com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 18 publications
1
24
1
Order By: Relevance
“…Based on a recent review which discussed water as source of H pylori, it was concluded that even if confirmed as a reservoir for H pylori, water most likely would be only be a secondary route of transmission. 2 Our study did not show any 22 Other Helicobacter spp of animal origin such as Helicobacter canis (from dogs and cats), 23 Helicobacter pullorum (from poultry), 24 and Helicobacter suis (from pigs) 25 were found to cause infection in human.…”
Section: Re Sultscontrasting
confidence: 55%
See 1 more Smart Citation
“…Based on a recent review which discussed water as source of H pylori, it was concluded that even if confirmed as a reservoir for H pylori, water most likely would be only be a secondary route of transmission. 2 Our study did not show any 22 Other Helicobacter spp of animal origin such as Helicobacter canis (from dogs and cats), 23 Helicobacter pullorum (from poultry), 24 and Helicobacter suis (from pigs) 25 were found to cause infection in human.…”
Section: Re Sultscontrasting
confidence: 55%
“…On the other hand, higher seroprevalence was reported in children with sheep contact compared to children without sheep contact in Poland . Other Helicobacter spp of animal origin such as Helicobacter canis (from dogs and cats), Helicobacter pullorum (from poultry), and Helicobacter suis (from pigs) were found to cause infection in human.…”
Section: Discussionmentioning
confidence: 98%
“…H. canis DNA has also been detected in the feces of children shown to be transiently positive for H. pylori (Haggerty et al 2005). It has also been isolated from a number of immuno-deficient patients with bacteremia, including a patient with X-linked hypogammaglobulinemia (Gerrard et al 2001), a patient with gastric lymphoma (Alon et al 2010) and a woman with common variable immune deficiency and liver failure (Abidi et al 2013). H. canis has also been isolated from two immune-competent patients, one with bacteremia (Leemann et al 2006), and the other a 7-month old child with bacteremia (Prag et al 2007).…”
Section: Helicobacter Canismentioning
confidence: 95%
“…H. canis has been identified in Bengal cats with diarrhoea (Foley et al, 1999), dogs with hepatitis (Fox et al, 1996a) and diarrhoea (Castiglioni et al, 2012;Stanley et al, 1993) and humans with gastroenteritis , autoimmune hepatitis (Casswall et al, 2010), inflammatory bowel disease (Tankovic et al, 2011) and bacteriemia (Abidi et al, 2013;Prag et al, 2007;Leemann et al, 2006;Gerrard et al, 2001). H. bilis has been associated with human chronic cholecystitis and biliary cancer (Matsukura et al, 2002;Fox et al, 1998) and with inflammatory bowel disease in mice (Maggio-Price et al, 2006).…”
Section: Introductionmentioning
confidence: 99%